Is Isolated Nocturnal Hypertension A Reproducible Phenotype? - Abdalla, Marwah; Goldsmith, Jeff; Muntner, Paul; Diaz, Keith M; Reynolds, Kristi; Schwartz, Joseph E; Shimbo, Daichi (American journal of hypertension, 2016)
Isolated nocturnal hypertension (INH), defined as nocturnal without daytime hypertension on ambulatory blood pressure (BP) monitoring (ABPM), has been observed to be associated with an increased risk of cardiovascular disease (CVD) events and mortality. The aim of this study was to determine the short-term reproducibility of INH. The Improving the Detection of Hypertension Study enrolled a community-based sample of adults (N = 282) in upper Manhattan without CVD, renal failure, or treated hypertension. Each participant completed two 24-hour ABPM recordings (ABPM1: first recording and ABPM2: second recording) with a mean ± SD time interval of 33 ± 17 days between recordings. Daytime hypertension was defined as mean awake systolic/diastolic BP ≥ 135/85 mm Hg; nocturnal hypertension as mean sleep systolic/diastolic BP ≥ 120/70 mm Hg; INH as nocturnal without daytime hypertension; isolated daytime hypertension (IDH) as daytime without nocturnal hypertension; day and night hypertension (DNH) as daytime and nocturnal hypertension, and any ambulatory hypertension as having daytime and/or nocturnal hypertension. On ABPM1, 26 (9.2%), 21 (7.4%), and 50 (17.7%) participants had INH, IDH, and DNH, respectively. On ABPM2, 24 (8.5%), 19 (6.7%), and 54 (19.1%) had INH, IDH, and DNH, respectively. The kappa statistics were 0.21 (95% confidence interval (CI) 0.04-0.38), 0.25 (95% CI 0.06-0.44), and 0.65 (95% CI 0.53-0.77) for INH, IDH, and DNH respectively; and 0.72 (95% CI 0.63-0.81) for having any ambulatory hypertension. Our results suggest that INH and IDH are poorly reproducible phenotypes, and that ABPM should be primarily used to identify individuals with daytime hypertension and/or nocturnal hypertension.